Social Edupreneurship Innovation to Strengthen Literacy and Numeracy of Elementary and Middle School Students in Dharmasraya Regency - Ali Idrus; Dodi Widia Nanda; Ratih Utami Ramadhaniati; Muhamad Aman; Tri Saswandi (The Future of Education Journal, 2026)
This study discusses social edupreneurship innovation as an effort to strengthen literacy and numeracy among elementary and junior high school students in Dharmasraya Regency. The main issue addressed is the uneven development of students’ abilities in reading, understanding information, performing calculations, and applying mathematical concepts in everyday life. These conditions are influenced by limited learning resources, differences in students’ abilities, low levels of family support, and the suboptimal use of learning data in schools. To address these issues, this study proposes the concept of the Village Literacy and Numeracy Center as a community-based learning model. This program connects schools, families, village governments, volunteers, and local communities through guided reading activities, reading corners, diagnostic classes, contextual numeracy laboratories, as well as mentoring programs for teachers and parents. The uniqueness of the program lies in its use of local community life as a learning resource, such as village markets, agricultural products, folklore, and local economic activities. Through this approach, literacy and numeracy are understood not only as academic competencies but also as essential life skills. The program also emphasizes simple evaluation through student progress data, enabling teachers to adjust learning strategies according to students’ actual needs. This study highlights that strengthening basic education must be carried out collaboratively, simply, equitably, and sustainably in order to reduce learning disparities and build a strong educational culture at the village level through the active and responsible involvement of all community elements.